Coexistence of the Oxazolidinone Resistance–Associated Genes cfr and optrA in Enterococcus faecalis From a Healthy Piglet in Brazil - Almeida, Lara M.; Gaca, Anthony; Bispo, Paulo M.; Lebreton, François; Saavedra, Jose T.; Silva, Rafael A.; Basílio-Júnior, Irinaldo D.; Zorzi, Felipe M.; Filsner, Pedro H.; Moreno, Andrea M.; Gilmore, Michael S. (Frontiers in Public Health, 2020)
Oxazolidinones are one of the most important antimicrobials potentially active against glycopeptide- and β-lactam–resistant Gram-positive pathogens. Linezolid – the first oxazolidinone to be approved for clinical use in 2000 by the US Food and Drug Administration – and the newer molecule in the class, tedizolid, inhibit protein synthesis by suppressing the formation of the 70S ribosomal complex in bacteria. Over the past two decades, transferable oxazolidinone resistance genes, in particular cfr and optrA, have been identified in Firmicutes isolated from healthcare-related infections, livestock, and the environment. Our goals in this study were to investigate the genetic contexts and the transferability of the cfr and optrA genes, and examine genomic features, such as antimicrobial resistance genes, plasmid incompatibility types, and CRISPR-Cas defenses of a linezolid-resistant Enterococcus faecalis isolated in feces from an healthy pig during an antimicrobial surveillance program for animal production in Brazil. The cfr gene was found to be integrated into a transposon-like structure of 7,759 nt flanked by IS1216E and capable of excising and circularizing, distinguishing it from known genetic contexts for cfr in Enterococcus spp., while optrA was inserted into an Inc18 broad host-range plasmid of >58 kb. Conjugal transfer of cfr and optrA was shown by filter mating. The coexistence of cfr and optrA in an E. faecalis isolated from a healthy nursery pig highlights the need for monitoring the use of antibiotics in the Brazilian swine production system for controlling spread and proliferation of antibiotic resistance.